2020
DOI: 10.1177/1369433219896166
|View full text |Cite
|
Sign up to set email alerts
|

Seismic damage features of high-speed railway simply supported bridge–track system under near-fault earthquake

Abstract: Seismic loads pose a potential threat to the high-speed railway bridges in China, which have been rapidly developing in recent years, especially for those subjected to the near-fault earthquakes. The previous researches on high-speed railway bridges usually concern the far-field earthquake, and the damage of high-speed railway bridge–track system subjected to the near-fault earthquake has not been well studied. In this article, a seven-span high-speed railway simply supported bridge–track system is selected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The Effect of fling-step motion on seismic performance evaluated by some observations, two serious regions of the CFST arch where the arch foot is subjected to the buckling load tube tearing due to the initial compressive state of the arch rib under the gravity action and the strain index investigation has shown that the microscopic strain distribution significantly different than the macroscopic dynamic indices (Xin et al, 2019). Wei et al (2018), investigated the damager features of different main components in HSR Simply supported HSR Bridge under near fault earthquake, the results proved that the background excitations with high frequency motions produced nearly 90% of the pier displacement response, 80% of the sliding layer response, and 85% of the shear alveolar response and concluded that the sliding layer and the shear alveolar are the weakest components which leads to failure of the track system (Guo et al, 2020).…”
Section: Effect Of Near-fault Earthquake On Bridge Structuresmentioning
confidence: 97%
“…The Effect of fling-step motion on seismic performance evaluated by some observations, two serious regions of the CFST arch where the arch foot is subjected to the buckling load tube tearing due to the initial compressive state of the arch rib under the gravity action and the strain index investigation has shown that the microscopic strain distribution significantly different than the macroscopic dynamic indices (Xin et al, 2019). Wei et al (2018), investigated the damager features of different main components in HSR Simply supported HSR Bridge under near fault earthquake, the results proved that the background excitations with high frequency motions produced nearly 90% of the pier displacement response, 80% of the sliding layer response, and 85% of the shear alveolar response and concluded that the sliding layer and the shear alveolar are the weakest components which leads to failure of the track system (Guo et al, 2020).…”
Section: Effect Of Near-fault Earthquake On Bridge Structuresmentioning
confidence: 97%
“…There is a global tendency to use numerical models with high level of complexity and details to assess the comprehensive behavior of structures. Nevertheless, due to the high demand for computational resources, simplified models that consider concentrated plastic hinges (Guo et al, 2020; Zheng et al, 2015), as well as those that consider fiber elements (Chen and Li, 2020; Hassan and Billah, 2020; Su et al, 2020; Zhang et al, 2020), are well established. Although these simplified models allow numerical simulations with low computational cost, the applicability of simplified models to represent damage in RC elements needs to be deeply studied (Su et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the seismic analysis of the railway bridge-track system built on the mountainous topography needs to consider two negative effects: (i) the dynamic characteristics and seismic responses of adjacent spans of irregular bridges (such as different pier heights, different bridge types, etc.) are different due to various topographies [3,4]; (ii) the spatial variability effect of ground motion distribution caused by local site and irregular topography leads to different parameters of ground motion excitation at different pier locations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%